Climate Finance - Stefano Giglio; Bryan Kelly; Johannes Stroebel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We review the literature studying interactions between climate change and financial markets. We first discuss various approaches to incorporating climate risk in macro-finance models. We then review the empirical literature that explores the pricing of climate risks across a large number of asset classes including real estate, equities, and fixed income securities. In this context, we also discuss how investors can use these assets to construct portfolios that hedge against climate risk. We conclude by proposing several promising directions for future research in climate finance.
Keywords: 330; climate change; climate risk; physical risk; transition risk; ESG